2012
DOI: 10.1080/1554480x.2012.715740
|View full text |Cite
|
Sign up to set email alerts
|

Representation radio: digital art-making as transformative pedagogical practice in the college classroom

Abstract: In this article, the authors unpack a first-year college seminar where students explored digital representations of self-afforded pedagogies of possibility for traditionally marginalized student populations, specifically students of colour and first-generation college goers. An artefact analysis model is used to trace the relationship between the design decisions we made about the course and what these decisions afforded students in terms of their understanding of the relationship between identity, narrative a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…The literature that connected subject matter to first-generation college students’ lived experiences showed that such connections facilitate these students’ academic learning. For instance, Bass and Halverson (2012) found first-generation college students in their study valued being able to examine and draw on their own lives in their learning of subject-matter concepts in a first-year interest group course. Castillo-Montoya (2017) found racially and ethnically diverse first-generation college students had ways of thinking and knowing that faculty helped unpack as valuable prior knowledge that could enhance subject-matter learning.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The literature that connected subject matter to first-generation college students’ lived experiences showed that such connections facilitate these students’ academic learning. For instance, Bass and Halverson (2012) found first-generation college students in their study valued being able to examine and draw on their own lives in their learning of subject-matter concepts in a first-year interest group course. Castillo-Montoya (2017) found racially and ethnically diverse first-generation college students had ways of thinking and knowing that faculty helped unpack as valuable prior knowledge that could enhance subject-matter learning.…”
Section: Resultsmentioning
confidence: 99%
“…For teachers who want to support and empower first-generation college students as academic learners who can interconnect their lives and subject matter and engage in multidirectional learning, we recommend the following. First-generation college students benefit from academic experiences that center communal and prosocial goals (e.g., Harackiewicz et al, 2014), create classroom community with instructors and peers (e.g., Schademan & Thompson, 2016; Wirt & Jaeger, 2014), draw on their lived experiences (e.g., Bass & Halverson, 2012; Castillo-Montoya, 2017), and provide them with explicit tools for navigating the academy and academic resources (e.g., Faulkner & Burdenski, 2011; Yee, 2016). Simultaneously teaching first-generation college students about mainstream academic culture, while valuing their own cultures, empowers them to be more fully themselves in their academic success (e.g., Jehangir, 2009; Morales, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Fourthly, this research adds to the small yet promising body of work on community radio and young people (for an overview of this body of work see Wilkinson, 2015). A key focus for this research has been on how community radio can empower and give 'voice' to young people from disadvantaged groups (see Bass and Halverson, 2012;Doerr-Stevens, 2011;Kelly, 2015;Marchi, 2009;Podkalicka and Staley, 2009;Wagg, 2004;Wilkinson, 2016, Wilkinson, 2018b, as well as its role in fostering intergenerational community relations (see Chávez and Soep, 2005). Both of these elements are important to our project and to the radio station involved (KCC Live) as we aimed to allow young people living in one of the most deprived areas of the UK v to produce their own media representations in contrast to dominant media representations of youth, and to do so via engagement with intergenerational community memories.…”
Section: Examining Representations Of Urban Youth and Riots Through Hmentioning
confidence: 99%